2017
DOI: 10.1186/s12885-016-2996-4
|View full text |Cite
|
Sign up to set email alerts
|

A non-invasive tool for detecting cervical cancer odor by trained scent dogs

Abstract: BackgroundCervical Cancer (CC) has become a public health concern of alarming proportions in many developing countries such as Mexico, particularly in low income sectors and marginalized regions. As such, an early detection is a key medical factor in improving not only their population’s quality of life but also its life expectancy. Interestingly, there has been an increase in the number of reports describing successful attempts at detecting cancer cells in human tissues or fluids using trained (sniffer) dogs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 26 publications
(21 reference statements)
0
29
0
Order By: Relevance
“…Their functions span from olfaction to sperm chemotaxis, to regulation of renal function, to regeneration and migration in muscle cells, or to neuronal regulation (Spehr et al, 2004 ; Griffin et al, 2009 ; Pluznick et al, 2009 ; Grison et al, 2014 ; Ferrer et al, 2016 ). hORs are connected to several diseases, including cervical cancer, prostate cancer, pancreatic ductal adenocarcinoma, Creutzfeldt-Jakob's disease, Alzheimer's disease, progressive supranuclear palsy, schizophrenia, and retinitis pigmentosa (Wang et al, 2006 ; Neuhaus et al, 2009 ; Kang and Koo, 2012 ; Zhou et al, 2012 ; Ansoleaga et al, 2013 ; Rodriguez et al, 2014 ; Ma et al, 2015 ; Guerrero-Flores et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Their functions span from olfaction to sperm chemotaxis, to regulation of renal function, to regeneration and migration in muscle cells, or to neuronal regulation (Spehr et al, 2004 ; Griffin et al, 2009 ; Pluznick et al, 2009 ; Grison et al, 2014 ; Ferrer et al, 2016 ). hORs are connected to several diseases, including cervical cancer, prostate cancer, pancreatic ductal adenocarcinoma, Creutzfeldt-Jakob's disease, Alzheimer's disease, progressive supranuclear palsy, schizophrenia, and retinitis pigmentosa (Wang et al, 2006 ; Neuhaus et al, 2009 ; Kang and Koo, 2012 ; Zhou et al, 2012 ; Ansoleaga et al, 2013 ; Rodriguez et al, 2014 ; Ma et al, 2015 ; Guerrero-Flores et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the following studies have demonstrated canine cancer detection for cancer screening is promising, feasible, and safe (Table 3) [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Detection threshold has been shown to be as low as 1.5 parts per trillion (ppt) [10]. Trained dogs can successfully discriminate between patients with cancers of skin [11,12], bladder [13], lung [14][15][16][17][18], breast [14,19,20], prostate [20][21][22] ovary [23][24][25], colorectal [19,26], liver [27], uterine cervix [28] from controls on the basis of odors in breath, urine, blood or cell culture medium. However, the canine cancer detection testing for breast cancer using human urine samples has not yet been attempted.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, these "anecdotal" events were not supported by evidence. However, the following studies have demonstrated canine cancer detection for cancer screening is promising, feasible, and safe (Table 3) [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Table 3 Published reports on canine detection of various cancer types.…”
Section: Discussionmentioning
confidence: 99%